The Role of Standing Variation in the Evolution of Weedines Traits in South Asian Weedy Rice (Oryza spp.). Issue 11 (1st November 2018) - Huang, Zhongyun; Kelly, Shannon; Matsuo, Rika; Li, Lin-Feng; Li, Yaling; Olsen, Kenneth M; Jia, Yulin; Caicedo, Ana L
Abstract: Weedy rice ( Oryza spp.) is a problematic weed of cultivated rice ( O. sativa ) around the world. Recent studies have established multiple independent evolutionary origins of weedy rice, raising questions about the traits and genes that are essential for the evolution of this weed. Among world regions, South Asia stands out due to the heterogeneity of its weedy rice populations, which can be traced to at least three origins: two through de-domestication from distinct cultivated rice varieties, and one from local wild rice ( O. rufipogon / O. nivara ). Here we examine five traits considered typical of or advantageous to weedy rice in weedy, cultivated and wild rice samples from South Asia. We establish that convergence among all three weed groups occurs for easy seed shattering, red pericarp color, and compact plant architecture, suggesting that these traits are essential for weed success in the South Asian agricultural environment. A high degree of convergence for black hull color is also seen among weeds with wild ancestors and weeds evolved from the aus cultivated rice group. We also examine polymorphism in five known domestication candidate genes, and find that Rc and Bh4 are associated with weed seed pericarp color and hull color, respectively, and weedy alleles segregate in the ancestral populations, as do alleles for the seed dormancy-linked gene Sdr4 . The presence of a domestication related allele at the seed shattering locus, sh4, in weedy rice populations with cultivated ancestry supports a de-domestication origin for these weedy groups, and raises questions about the reacquisition of the shattering trait in these weedy populations. Our characterization of weedy rice phenotypes in South Asia and their associated candidate genes contribute to the emerging understanding of the mechanisms by which weedy rice evolves worldwide, suggesting that standing ancestral variation is often the source of weedy traits in independently evolved groups, and highlighting the reservoir of genetic variation that is present in cultivated varieties as well as in wild rice, and its potential for phenotypic evolution.